2005
DOI: 10.1021/ja0552186
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Copper(I)−Fesulphos-Catalyzed 1,3-Dipolar Cycloaddition of Azomethine Ylides

Abstract: The catalyst system formed by Cu(CH3CN)4ClO4 and the planar chiral P,S-ligand Fesulphos behaves as a very efficient chiral Lewis acid in the catalytic asymmetric 1,3-dipolar cycloaddition of azomethine ylides. This catalyst shows a remarkable reactivity at low catalyst loading (0.5-3 mol %), affording in good yields the endo adducts with exceptional levels of enantioselectivity (up to >99% ee). This catalytic asymmetric procedure has a broad structural scope with regard to both azomethine and dipolarophile sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(90 citation statements)
references
References 18 publications
3
84
1
2
Order By: Relevance
“…The [3+2] cycloaddition reaction of azomethine ylide with olefinic dipolarophiles constitutes a straightforward approach to the synthesis of highly substituted chiral pyrrolidine derivatives. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] So far, many laboratories have reported the catalytic asymmetric [3+2] cycloadditions with azomethine ylides by means of a variety of ligand-metal combinations. Our group reported that the ferrocenyloxazoline derived chiral N,P ligand showed excellent performance in the Ag(I)-catalyzed enantioselective 1,3-dipolar cycloaddition of azomethine ylides.…”
Section: Resultsmentioning
confidence: 99%
“…The [3+2] cycloaddition reaction of azomethine ylide with olefinic dipolarophiles constitutes a straightforward approach to the synthesis of highly substituted chiral pyrrolidine derivatives. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] So far, many laboratories have reported the catalytic asymmetric [3+2] cycloadditions with azomethine ylides by means of a variety of ligand-metal combinations. Our group reported that the ferrocenyloxazoline derived chiral N,P ligand showed excellent performance in the Ag(I)-catalyzed enantioselective 1,3-dipolar cycloaddition of azomethine ylides.…”
Section: Resultsmentioning
confidence: 99%
“…2) and Cu(MeCN) 4 ClO 4 (3 mol%) as catalytic mixture was employed in the reaction of -nitrostyrene 10 (R 1 = Ph) and methyl benzylideneaminoglycinate 6 (R 3 = Ph, R 4 = H, R 5 = Me) with triethylamine as base (18 mol%) in dichloromethane at -10 ºC. The corresponding exo-cycloadduct 5 was isolated as major diastereoisomer (95:5 dr) in moderate yield (61%) and high enantioselection (94% ee) following the general reaction shown in (Scheme 7) [50,51].…”
Section: Chiral Copper Complexes As Catalystsmentioning
confidence: 99%
“…The bioprospection of spirooxindoles 3 has been analyzed following the zebrafish embryo model determining. The LC 50 values indicated elevated mortality of embryos in several tests [7]. Hybrid molecules 4 with benzopyran skeleton were successfully tested as antimycobacterials against M.tuberculosis H37Rv strain [8].…”
Section: Introductionmentioning
confidence: 99%
“…The most simple prolinesexo-46 have been recently used as chiral organocatalysts in aldol reactions [ 79 ]. In particular, for the asymmetric 1,3-DC of nitroalkenes as dipolarophiles chiral copper(I) complexes, formed from ferrocenyl-type phosphanes, have been mainly used as catalysts [80,81,82,83,84,85].Copper(I) complexes 47 [80,82], 48 [81,83], and 49 [79], generally afforded exo-cycloadducts, whereas the corresponding endo-diastereomers have been prepared using complex 50 [79]. On the other hand, when copper(II) triflate and chiral ligand PyBidine [86] were combined the resulting catalyst 51afforded mainly endo-cycloadducts.…”
Section: Copper-catalyzed 13-dc Of Azomethine Ylides and Nitroalkenesmentioning
confidence: 99%